All That Wheezes Is Not Asthma: A Case of Diffuse Large B-Cell Lymphoma of the Larynx - Bushra Rahman; Jawad Bilal; Qurat Ul Ain Riaz Sipra; Irbaz Bin Riaz (Case Reports in Oncological Medicine)
Localized laryngeal lymphoma is a rare entity with an incidence of less than 1% of all laryngeal neoplasms. Diffuse large B-cell lymphoma (DLBCL) is the most common type of laryngeal neoplasms. Here, we describe a case of a young 28-year-old female with large B-cell lymphoma who remained undiagnosed for a long time owing to a myriad of nonspecific presentation including “wheezing.” Although primary laryngeal lymphomas constitute a diagnostic challenge since they are rare, one should have a high index of suspicion for lymphoma of the larynx in patients presenting with unresolved wheezing as it can present catastrophically with acute airway obstruction requiring immediate surgical intervention which was observed in this case. Treatment includes radiotherapy, chemotherapy, immunotherapy, or a combination of these. We hope that the discussions ensuing from case reports regarding uncommon presentations of laryngeal lymphoma may spur the formation of regional/international databases for the description of lymphomas with unusual presentations. This effort can lead to in-depth study of cases and prompt awareness of “rare and subtle presentations” of laryngeal lymphoma.